ANALYSIS OF MARKETING - MIX AND RELIABILITY FACTORS RELATED TO THE DECISION TO PURCHASE ONLINE VOLUNTARY AUTOMOBILE INSURANCE IN TRANG PROVINCE - Chuarkham, Khanchit; Yohmad, Saranya; Duangmanee, Krittiya (Journal of MCU Nakhondhat, 2021)
The Objectives of this research article were to conduct an analysis of factors related to the marketing mix and reliability that have an impact on members of the public’s decision whether or not to purchase online voluntary automobile insurance in Trang Province in the south of Thailand. This was a quantitative research study, examining a sample that consisted of 400 Trang residents. Non - probability sampling was rolled out in two stages: 1) quota sampling, involving 10 districts with 40 people in each district, and 2) accidental sampling in all the districts concerned. Questionnaires were used as a research tool, and data were analysed by taking a look at a number of parameters, namely frequency, percentage, average value, standard deviation and chi - square statistics. The results make it clear that the main reasons why most of those belonging to the sample had not bought voluntary automobile insurance online were, first and foremost, insufficient confidence in the after - sales service, unlike buying insurance from an agent; and, second, their need for advice from staff or agents regarding the coverage. In addition, as for factors pertaining to the marketing mix, the choice made by customers whether to buy insurance was affected by the price and the product: they prioritised above all having a variety of premiums to compare with other companies, and, next, having a delivered policy that was both comprehensive and correct. In contrast, there was no association between market promotion and clients’ buying decision. However, factors connected to the reliability of the website and the company were linked to the decision to make the relevant purchase. For customers, the top priority in this respect was the clarity and comprehensiveness of the information about voluntary automobile insurance, and this was followed by the stability and long - term future of the company.